Nonverbal communication between veterinarian and farmer during routine consultations on UK dairy farms - MacGillivray, Fiona (2022)
Research objective: To explore whether nonverbal communication between veterinarians and farmers can be measured through analysis of video recordings of routine consultations on farm.